Self-delusion in the pursuit of happiness - Dag Einar Sommervoll (Statistics Norway, Research Department, 2010)
The paper explores how repeated revisions of consumption plans increase long-run utility. If agents value present anticipations of future consumption, some revisions may be viewed as a benign form of self-delusion. We consider a minimal generalization of the Samuelson discounted utility model to allow for utility linked to next period consumption. Agents are assumed to vary with respect to their sophistication. Different environments likely to facilitate repeated revisions are also considered.
Keywords: A12; B49; C70; D11; D60; D74; D91; E21; 330